Perspectives, opinions, and perceptions of pastoralists on their sustainability: the case of the Pyrenean region of Pallars in Spain - Lecegui A.; Vidal-Mones B.; López-i-Gelats F.; Varela E. (Pastoralism and sustainable development: proceedings, 2021)
Traditional small-scale livestock farming activity in the Spanish Eastern Pyrenees is nowadays influenced by market globalization trends as well as regional factors such as nature protection regulations and tourism. This study addressed pastoralists´ perspectives, opinions, and perceptions regarding the challenges that threaten their sustainability. We carried out a face-to-face survey with 103 pastoralists in Pallars (Catalonia) during 2018. The stagnation in sales’ prices of products was considered the biggest challenge and one of the underlying causes of the farms’ low financial profitability. Pastoralists also pointed out the highly burdening bureaucracy, the lack of generational turnover, and the difficult coexistence with wildlife as important problems undermining the livestock sector in the region. Although most participants positively considered their increasingly valued role in the conservation of biodiversity, their perception of protected natural areas was mostly negative. Respondents reported a total of 613 conflicts with wildlife during the previous year. Wild boars were the species most frequently mentioned for damaging meadows, crops, and infrastructures, causing road accidents, and disease transmission. Vultures were held responsible for attacks on flocks while deer species were signalled for fodder competence. These results confirm the multiple adverse menace factors of pastoralism and highlight the urgent need to establish favourable policies that involve local actors in decision-making processes to overcome these obstacles.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)